Peningkatan Motivasi Belajar IPAS Melalui Penggunaan Media Kokami (Kotak Kartu Misteri) Materi Tumbuhan Siswa Kelas IV SD Plus Melati Samarinda - Nur Ilmiah; Marniati Kadir; Siti Aminah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the improvement of student learning motivation in the Natural and Social Science (IPAS) subject on plant material through the application of Kokami (Mystery Card Box) media in Grade IV of SD Plus Melati Samarinda. Low student motivation, characterized by passive attitudes, inattentiveness, and easy boredom, formed the basis for conducting this research. The method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model comprising four stages: planning, acting, observing, and reflecting, conducted over two cycles. The research subjects consisted of 25 Grade IV students. Data collection instruments included student motivation observation sheets and teacher activity observation sheets. Data were analyzed using a percentage formula. The findings reveal a significant improvement in learning motivation: at the pre-cycle stage, the average percentage was only 35.3% (low category), rising to 70% in Cycle I (good category), and reaching 90% in Cycle II (very good category). All learning motivation indicators surpassed the minimum success threshold of 80%, confirming the success of this research. Kokami media proved effective in creating an interactive, enjoyable, and challenging learning atmosphere for elementary school students.